Exploring the effectiveness of the Career Guidance and Counseling Program on the perceived readiness for the job market: a lived experience among nursing students - Alnajjar, Hend Abdu; Abou Hashish, Ebtsam Aly (Frontiers in Public Health, 2024)
Background: The current workforce demands that nursing graduates possess the necessary skills and knowledge to perform in complex clinical and professional environments. Career guidance can potentially improve students' job readiness by increasing their confidence in career pursuits, simplifying career decisions, and helping them address decision-making challenges. Methods: This phenomenological study aimed to explore nursing students and interns’ perspectives on the effectiveness of the Career Guidance and Counseling Program (CGCP) and its impact on their readiness for the job market through their lived experiences while participating in the program. Data were collected through in-depth semi-structured interviews with a purposive sample of 28 Saudi university students and continued until data saturation was reached. Thematic analysis was used for the data analysis. Results: Seven themes emerged: personal experiences with the CGCP, the program's importance, effectiveness, benefits, strengths, and weaknesses, and recommendations for improvement. Overall, participants expressed gratitude for the CGCP and believed that it would positively impact their future career success. They also felt that the program provided them opportunities to share ideas, information, and concerns, thereby improving their career decision-making and adaptability. Conclusions: The results show that CGCP positively affected participants' lives by providing support, guidance, and resources for informed career decision-making, developing essential career-related skills, and navigating career transitions. These findings have practical implications for nursing colleges implementing similar programs for better integration into the curriculum and for the continuity of such vital programs to help students. Future studies should explore this topic in different colleges and specialties. Keywords: Career guidance and counseling program, lived experience, nursing students, job market.